Characterization of a Novel Cellulosic Fiber from Brassica oleracea Var. Italic Stem - Seyda Eyupoglu (Journal of Natural Fibers, 2022)
This study targets to investigate the properties and morphology of fibers obtained from the stem of Brassica oleracea var. Italic known as broccoli plant. The morphology and diameter of the Brassica oleracea var. Italic fibers (BOVIFs) were analyzed using a scanning electron microscopy. The elemental components were determined by energy-dispersive X-ray analysis. The functional groups of BOVIFs were studied by a Fourier transform-infrared instrument. The thermal degradation behavior was assessed by thermogravimetric analysis/differential thermogravimetric analysis, and the crystallinity was specified with X-ray diffraction technique. Furthermore, the mechanical behaviors of BOVIFs were analyzed with Shimadzu Ag-X machine. The density and diameter of the fibers were specified as 1.80 g/cm3 and 585 µm. The energy-dispersive X-ray analysis results of BOVIFs show that the fiber consists of carbon (54.49%) and oxygen (45.34%). The cellulose and lignin contents present in the fiber are 47.8% and 13.4%, respectively. According to the Fourier transform infrared analysis, the fibers have a lignocellulose structure. The maximum peak temperature was determined at 365.05°C in the differential thermogravimetric analysis curve, and the crystallinity index was calculated as 70.19%. The fibers have a tensile strength of 790 MPa, an elongation at break of 4.30%, and a Young’s modulus of 18 GPa. The experimental results of this study show that BOVIFs can be used as a new plant-based fiber in many areas.